2015
DOI: 10.1308/003588414x14055925060839
|View full text |Cite
|
Sign up to set email alerts
|

Durability of giant hiatus hernia repair in 455 patients over 20 years

Abstract: INTRODUCTION The surgical management of symptomatic giant hiatus hernia (GHH) aims to improve quality of life (QoL) and reduce the risk of life threatening complications. Previous reports are predominantly those with small sample sizes and short follow-up periods. The present study sought to assess a large cohort of patients for recurrence and QoL over a longer time period. METHODS This was a follow-up study of a prospectively collected database of 455 consecutive patients. Primary repair of GHH was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 28 publications
(41 reference statements)
4
31
1
5
Order By: Relevance
“…However, patients with radiological evidence of failure or recurrent symptoms had a small but significant reduction in the QoL scores compared to patients without recurrence. The impact of recurrent hiatus hernia on symptoms after repair in our study was different to other large series where QoL appeared not to be affected following recurrence . In our patients, oesophagitis was common after recurrence, and Barrett's oesophagus was found in two patients.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…However, patients with radiological evidence of failure or recurrent symptoms had a small but significant reduction in the QoL scores compared to patients without recurrence. The impact of recurrent hiatus hernia on symptoms after repair in our study was different to other large series where QoL appeared not to be affected following recurrence . In our patients, oesophagitis was common after recurrence, and Barrett's oesophagus was found in two patients.…”
Section: Discussioncontrasting
confidence: 99%
“…The impact of recurrent hiatus hernia on symptoms after repair in our study was different to other large series where QoL appeared not to be affected following recurrence. 9,12,14 In our patients, oesophagitis was common after recurrence, and Barrett's oesophagus was found in two patients. Aly et al also identified a significant rate of Barrett's epithelium of 13% on preoperative endoscopy.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Как известно, чем больше размер ПОД, соответственно, выше риск развития рецидива после оперативных вмешательств по поводу ГПОД, так как создается избыточное натяжение сшиваемых ножек диафрагмы с возможностью последующего прорезывания швов [2]. Число рецидивов может достигать 66%, особенно при больших и гигантских ГПОД [3]. Это объясняется тем, что до сих пор не существует единого алгоритма при выполнении пластики ПОД, как и остается нерешенным вопрос об использовании сетчатых имплантатов.…”
Section: оригинальные статьиunclassified